Angular Superresolution Based on A Priori Information. Issue 3 (25th February 2021) - Lagovsky, B.; Samokhin, A.; Shestopalov, Y.
Abstract: The results of theoretical studies and mathematical modeling indicate the possibility of obtaining the angular superresolution and its limits by using algebraic methods of imaging. The necessary algorithms are created on the basis of solution to inverse problems. The limiting levels of the achieved angular superresolution are found depending on the signal‐to‐noise ratio for objects of various types. A number of specific advantages of the method are shown as applied to the solution of two‐dimensional problems. Capabilities of the method are illustrated by examples. High performance of the proposed approach allows one to use it in real time when scanning and tracking targets. Key Points: The proposed methods for processing the results of observations can improve the effective resolution in one‐ and two‐dimensional problems The use of a priori information allows one to strongly increase the quality of solutions